Diagnostic Performance of Fluorine-18-Fluorodeoxyglucose Positron Emission Tomography in the Postchemotherapy Management of Patients with Seminoma: Systematic Review and Meta-Analysis. (15th May 2014) - Treglia, Giorgio; Sadeghi, Ramin; Annunziata, Salvatore; Caldarella, Carmelo; Bertagna, Francesco; Giovanella, Luca
Abstract : Objective . To meta-analyze published data about the diagnostic performance of fluorine-18-Fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) and PET/computed tomography (PET/CT) in the postchemotherapy management of patients with seminoma. Methods . A comprehensive literature search of studies published through January 2014 on this topic was performed. All retrieved studies were reviewed and qualitatively analyzed. Pooled sensitivity and specificity, positive and negative predictive values (PPV and NPV), accuracy, and area under the summary ROC curve (AUC) of 18 F-FDG-PET or PET/CT on a per examination-based analysis were calculated. Subgroup analyses considering the size of residual/recurrent lesions were carried out. Results . Nine studies including 375 scans were selected. The pooled analysis provided the following results: sensitivity 78% (95% confidence interval (95% CI): 67–87%), specificity 86% (95% CI: 81–89%), PPV 58% (95% CI: 48–68%), NPV 94% (95% CI: 90–96%), and accuracy 84% (95% CI: 80–88%). The AUC was 0.90. A better diagnostic accuracy of 18 F-FDG-PET or PET/CT in evaluating residual/recurrent lesions >3 cm compared to those <3 cm was found. Conclusions . 18 F-FDG-PET and PET/CT were demonstrated to be accurate imaging methods in the postchemotherapy management of patients with seminoma; nevertheless possible sources of false-negative and false-positive results should be considered. The literature focusing on this setting still remains limited and cost-effectiveness analyses are warranted.